PENINGKATAN KETERAMPILAN MENULIS KARANGAN DESKRIPSI MENGGUNAKAN LINGKUNGAN SEKITAR DI KELAS V SEKOLAH DASAR - Aprilia, Nia; Halidjah, Siti; Sugiyono, Sugiyono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis researchaims to improve the description writing skills using the surrounding environment as a learning resource. The research procedure consists of planning, implementing, observing, and reflecting. Research subjects were teachers and students of grade V B, amounting to 17 people. Data collection techniques in the form of observing and observing documents. Data analysis techniques by means of qualitative analysis used to analyze data in the form of observation sheets of teachers' abilities are calculated by the mean formula. Student improvement observation sheets are calculated by percentage formula. The students' skill in writing essay description shows that the first cycle of the average score of students, 66.01 increased in the second cycle to 79.74 then increased to 84.97 in the third cycle with an increase of 5.23. The percentage of completeness in the first cycle was only 35.29%, increasing in the second cycle to 76.47%, increasing again in the third cycle to 88.24%. Thus it can be concluded that learning to use the surrounding environment can improve the writing skills of the description grade V B students on Public Elementary School 38 Sungai Kakap.Â  Keywords: Description Writing, Writing Skills, Surrounding Environment